Pembelajaran Tari di Sekolah Menengah Atas (SMA) di Yogyakarta: Kajian Embodiment dan Multikulturalisme - Titik Putraningsih (Institut Seni Indonesia Yogyakarta, 2020)
The Character Education through Arts: An Analysis of the Dance Learning Process in High Schools. This research aims to describe the practice of character education through the dance learning process in high schools, criticizing high schools’ approach for instilling character education to an attitude of tolerance and appreciative towards cultural diversity in Indonesia. It s qualitative research with an ethnocoreology and multicultural approach. The study used a purposive sampling method to determine the sample and selected schools that develop a multicultural educational dimension. The ethnocoreology approach is to observe embodiment experiences to the students who study local dance and Nusantara dance. A Multicultural approach is applied to monitor education for empowerment by using Ki Hadjar Dewantara’s Arts Education concept at schools. Data collection was conducted by observation, field study, literature, interviews, and documentation. Matthew B. Milles and A. Michael Huberman’s data reduction stages, data exposure, and concluding were used to analyze the data.The research findings show that (1) dance learning in high schools is an educational tool and an appropriate means to instill character education. It is an effort to positively influence students’ lives as a tool to control the students’ souls towards beauty, nobility, and refinement to live harmoniously and empowered. (2) Character education in dance lessons is by applying to appreciate, expressing, and creating dance works. (3) From a multicultural education perspective, the experience of the dancers’ needs will foster an attitude of tolerance and appreciation.Keywords: character education; dance learning; high school